Evolution, dissemination, and genetic dynamics of the carbapenem resistance gene blaNDM in China - Xiaofeng Hu; Boqian Wang; Mingliang Chen; Mingliang Chen; Mingliang Chen; Kexin Li; Kexin Li; Zhixi Peng; Zhixi Peng; Lianqun Jin; Junjie Yue; Hui Chen; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundBlaNDM, which encodes a metallo-β-lactamase that can hydrolyze most β-lactam antibiotics, has become a serious public health concern in China. It is crucial to investigate the evolution, dissemination, and genetic dynamics of blaNDM to develop potential strategies to control the proliferation of blaNDM.MethodsIn this study, we collected 1021 blaNDM-positive isolates, which features 67 new genomes from our laboratory and 954 genomes from NCBI. Through epidemiological big data analysis, phylogenetic tree-based geographic transmission analysis, and upstream-downstream genetic clustering evolution analysis, we systematically analyzed the evolution, dissemination, and genetic dynamics of blaNDM-positive bacteria.ResultsAnalysis results indicate that blaNDM-5 is gradually supplanting blaNDM-1 in China and Acinetobacter has been replaced as the primary blaNDM-harboring genus by the Enterobacter, Escherichia, and Klebsiella, which are both within the Enterobacteriaceae family and more easily transmitted among humans. Furthermore, blaNDM-positive bacteria exhibit a distinct livestock-environment-human transmission cycle, while the phylogenetic diversity of blaNDM and tet(X)-co-carrying genera is progressively expanding with concomitantly enhanced resistance phenotypes. Currently, the predominant blaNDM-positive bacterial strains have likely disseminated from southwest China to coastal regions. We further identified multiple transposon structures beyond Tn125 that may facilitate blaNDM transfer.ConclusionsThe diversity of the blaNDM and its carrier bacterial strains is continuously increasing, and its transmission range is also expanding. Of greater concern, super-resistant strains co-harboring blaNDM and tet(X) genes exhibit high potential for imminent emergence in human populations. Considering that the blaNDM-carrier bacteria are increasingly adapted to inter-human spread, the analysis results above can provide methodological and data support for epidemiological surveillance, tracing, and early warning alerts.